Drag Reduction of Passenger Car Using Add-On Devices. (23rd March 2014) - Bansal, Ram; Sharma, R. B.
Abstract : This work proposes an effective numerical model using the Computational Fluid Dynamics (CFD) to obtain the flow structure around a passenger car with different add-on devices. The computational/numerical model of the passenger car and mesh was constructed using ANSYS Fluent which is the CFD solver and employed in the present work. In this study, numerical iterations are completed, and then aerodynamic data and detailed complicated flow structure are visualized. In the present work, a model of generic passenger car was developed using solidworks, generated the wind tunnel, and applied the boundary conditions in ANSYS workbench platform, and then testing and simulation have been performed for the evaluation of drag coefficient for passenger car. In another case, the aerodynamics of the most suitable design of vortex generator, spoiler, tail plates, and spoiler with VGs are introduced and analysed for the evaluation of drag coefficient for passenger car. The addition of these add-on devices are reduces the drag-coefficient and lift coefficient in head-on wind. Rounding the edges partially reduces drag in head-on wind but does not bring about the significant improvements in the aerodynamic efficiency of the passenger car with add-on devices, and it can be obtained. Hence, the drag force can be reduced by using add-on devices on vehicle and fuel economy, stability of a passenger car can be improved.